The Assistance of Farmer Community in Utilizing Rice Straw of Catfish Pool Mud as a Medium of Silk-Worm Cultivation in Tanjung Bintang Sub-District, Lampung Selatan Regency - Sudarman Sudarman; Yessy Velina (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2021)
The purpose of this study was to investigate the effect of different media compositions (straw and catfish pool mud) as a medium for cultivating silkworms on biomass and silkworm populations. This community service applied Participatory Action research (PAR) involving the farmers’ groups and farmer association Gabungan Kelompok Tani (GaPokTan) in Tanjung Bintang sub-district. They are paddy farmers and catfish cultivators with a total of 205 groups. The socialization activity was carried out through Focus Group Discussion (FGD), discussing any related topic about how to cultivate silkworms. Because the situation entered the New Normal era during the Covid 19 period, the FGD was carried out with procedures by applying social distancing and limiting participants to 10 people. Therefore, FGD was conducted two times. The study results showed that the sludge produced by catfish pond cultivation and fermented rice straw, which is known as waste, can provide benefits to the cultivation of silkworms that provide economic value to the community.